2000
DOI: 10.1007/s003830050011
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic detection of intrauterine intussusception resulting in ileal atresia complicated by meconium peritonitis

Abstract: A neonate with ileal atresia (IA) complicated by meconium peritonitis (MP) whose prenatal ultrasonography (US) detected an intrauterine intussusception (IUI) is reported. Fetal ascites, dilated bowel loops, and abdominal calcifications were identified on serial US from 25 weeks of gestation. Intestinal loops with high echogenecity and a "target-like" appearance suggestive of IUI were detected in the right lower quadrant. The 2,680-g male was delivered vaginally at term and underwent a laparotomy. Fibrous adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Review of the literature on the subject revealed 19 articles fulfilling the inclusion criteria (detailed description of ultrasound findings as well as correlation between the prenatal ultrasonographic patterns and clinical outcome), for a total of 56 additional cases (Estroff et al, 1992;Shyu et al, 1994;Konje et al, 1995;Yang et al, 1997;Ohmichi et al, 1997;Patole et al, 1998;Chitayat et al, 1998;Chalubinski et al, 1992;Reynolds et al, 2000;Seow et al, 2000;Shimotake et al, 2000;Leung et al, 2001;Pan et al, 2002;Mendez et al, 2003;Shyu et al, 2003;Chen et al, 2004;Amagada et al, 2004;Agboola et al, 2004;Piolat et al, 2005). Of the 19 articles, 13 were case reports (Shyu et al, 1994;Konje et al, 1995;Yang et al, 1997;Ohmichi et al, 1997;Patole et al, 1998;Reynolds et al, 2000;Seow et al, 2000;Shimotake et al, 2000;Mendez et al, 2003;Chen et al, 2004;Amagada et al, 2004;Agboola et al, 2004;Piolat et al, 2005). To establish a correlation between antenatal findings and postnatal outcome, we divided the total 69 cases, including our series, into four grades: (1) grade 0: isolated intra-abdominal calcifications (n = 18), (2) grade 1: intra-abdominal calcification and ascites (n = 17) or pseudocyst (n = 2), or bowel dilatation (n = 6), (3) grade 2: two associated findings (n = 20), and (4) grade 3: all sonographic features (n = 6) (Table 1 and Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Review of the literature on the subject revealed 19 articles fulfilling the inclusion criteria (detailed description of ultrasound findings as well as correlation between the prenatal ultrasonographic patterns and clinical outcome), for a total of 56 additional cases (Estroff et al, 1992;Shyu et al, 1994;Konje et al, 1995;Yang et al, 1997;Ohmichi et al, 1997;Patole et al, 1998;Chitayat et al, 1998;Chalubinski et al, 1992;Reynolds et al, 2000;Seow et al, 2000;Shimotake et al, 2000;Leung et al, 2001;Pan et al, 2002;Mendez et al, 2003;Shyu et al, 2003;Chen et al, 2004;Amagada et al, 2004;Agboola et al, 2004;Piolat et al, 2005). Of the 19 articles, 13 were case reports (Shyu et al, 1994;Konje et al, 1995;Yang et al, 1997;Ohmichi et al, 1997;Patole et al, 1998;Reynolds et al, 2000;Seow et al, 2000;Shimotake et al, 2000;Mendez et al, 2003;Chen et al, 2004;Amagada et al, 2004;Agboola et al, 2004;Piolat et al, 2005). To establish a correlation between antenatal findings and postnatal outcome, we divided the total 69 cases, including our series, into four grades: (1) grade 0: isolated intra-abdominal calcifications (n = 18), (2) grade 1: intra-abdominal calcification and ascites (n = 17) or pseudocyst (n = 2), or bowel dilatation (n = 6), (3) grade 2: two associated findings (n = 20), and (4) grade 3: all sonographic features (n = 6) (Table 1 and Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Although intrauterine intussusception has been described as dilatation of bowel loops [4], ascites with intraabdominal calcifications in perinatal ultrasound [5,6] or after carrying out a gastrografin enema before surgery [7], the definitive diagnosis is usually made after operating on a neonate with bowel occlusion and finding a jejunoileal atresia whose distal segment contains a polypoid protrusion [8,9], as our case demonstrates clearly.…”
Section: Discussionmentioning
confidence: 77%
“…Although the duodenum is the most common site, the jejunum and ileum account for 39% of cases of intestinal atresia 1 . Reports of prenatally‐diagnosed ileal atresia consist of case reports and small series, with sonographic detection typically occurring late in the third trimester 6–11 . Of our cases, 56.3% were antenatally‐diagnosed and all antenatally‐diagnosed cases were detected in the third trimester.…”
Section: Discussionmentioning
confidence: 78%
“…1 Reports of prenatally-diagnosed ileal atresia consist of case reports and small series, with sonographic detection typically occurring late in the third trimester. [6][7][8][9][10][11] Of our cases, 56.3% were antenatally-diagnosed and all antenatallydiagnosed cases were detected in the third trimester. The diagnosis of ileal atresia may be difficult because most cases are not apparent until the third trimester and the sonographic features are not unique.…”
Section: Discussionmentioning
confidence: 99%